Web Application Firewall (WAF) Design to Detect and Anticipate Hacking in Web-Based Applications - Annas, Muhammad; Adek, Rizal Tjut; Afrillia, Yesy (Journal of Advanced Computer Knowledge and Algorithms, 2024)
Data leakage cases have recently been rampant in Indonesia. One of the biggest is the leak of user data from BPJS Health in 2021, this data leak is certainly very detrimental to users. This research develops a Web Application Firewall (WAF) using ModSecurity and OWASP Core Rule Set to protect web applications from SQL Injection and XSS attacks. The methodology involves analyzing the functionality of the existing system using UML, with DVWA and WordPress as test objects. Results showed 100% SQL Injection and 99.8% XSS attack detection, with logs recording attacks in real-time. The findings emphasize the importance of WAF integration with web application built-in security, making significant contributions in the design and implementation of resilient WAFs, as well as improving resilience against evolving cyber threats.